Co-design of data collection with participants of the Aberdeen Children of the 1950s cohort study. (30th September 2020) - Johnston, M; Butler, J; Clark, H; Locock, L; Murray, A D; Robertson, L; Hannaford, P; Iversen, L; Skea, Z; Black, C
Abstract: Background: The Aberdeen Children of the 1950s (ACONF) cohort comprises 12, 150 people born in Scotland in the 50s. It contains rich early life data, questionnaire data from mid-life and linked electronic health records. Involving participants in designing future data collection is key to ensure research is acceptable and reflects public priorities. Aim: Gather ACONF members views to inform how to: research healthy ageing, optimise recruitment and maximise participation. Methods: 3 co-design workshops with 30 ACONF members. A discussion was led by a facilitator using guidance questions developed by the study team. Workshops were recorded and transcribed. Results: Participants viewed healthy ageing as keeping socially and physically active, taking responsibility for oneself and having a positive attitude to ageing. Research priorities were dementia, improvements in the social care system and engaging hard-to-reach groups. Members were keen for future research involvement. Recruitment may be maximised by: more information online, involving participants in recruiting other study members and clarity about potential benefits to themselves or others. It was acceptable to ask their offspring to participate. There were high levels of trust in researchers, but ongoing data protection is vital. Participation may be improved by regular contact (informing members of results, engagement events, phone "apps"). Participants viewed various data collection methods (questionnaires, applications, wearable devices, in-person tests, DNA collection and electronic record linkage) as acceptable. Conclusions: Participant involvement is a fundamental part of securing a social license for research. Participants were in favour of ongoing research, including recruitment of their children. The workshops highlighted key considerations for future research and data collection. Key messages: Co-design is vital for highlighting research topics which are important and relevant to the general population. Co-design can highlight strategies for maximising research participation and securing a social license for research.